Concepts of Arrangement of Artifical Teeth, Selective Grinding and Balanced Occlusion in Complete Denture Prosthodontics - D., Krishna Prasad; Prasad, B. Rajendra; D., Anupama Prasad; Jason, Lobo Nikhil (Journal of Health and Allied Sciences NU, 2012)
Prosthodontic rehabilitation aims at restoring the patient to a state of normal function, health and optimum esthetics.Numerous factors come together during various phases of complete denture construction. One such factor, the position of artificial teeth, is dependent to a large extent on the state, morphology and position of the denture area existing in the patient's mouth.Artificial teeth must be placed in a position which will be esthetically acceptable to the patient and the clinician, functionally sound and in harmony with the other structures of the masticatory system.Factors governing artificial tooth position include maxillo-mandibular relationships, changes in the residual ridge, dislodging forces, presence of para-functional activity and the esthetic requirements of the patient.While the importance of occlusion in ensuring success of dental therapy cannot be undersated, that seems to be the only point of agreement between authors on this topic. Over the years numerous concepts of occlusion have been proposed which may be indicated and contraindicated based on their benefits and limitations in restoring an edentulous patient. This article explores concepts related to occlusion and esthetics in provision of a complete denture prosthesis.
Keywords: complete denture; balanced occlusion; teeth arrangement; selective grinding; history of occlusion; dentogenics and dynesthetics